SUBPOPULATION PROFILES OF T HELPER CELLS EXPRESSING CD45RA AND CD31 MARKERS IN CHILDREN AFTER THYMECTOMY PERFORMED UPON SURGICAL TREATMENT OF CONGENITAL HEART DISEASE - Yu. I. Rovda; S. A. Shmulevich; A. V. Shabaldin; E. B. Lukoyanycheva (Медицинская иммунология, 2016)
Thymectomy is a stage of surgery when treating some congenital heart defects. Thymus gland is the central organ of immune system. This organ is the primary site of T-cell lymphopoiesis and central tolerance to autoantigens during fetal and early postnatal life. If performed neonatally or in infancy, the thymectomy may cause restriction of these immune functions. Suppression of T-cell lymphopoiesis in children with thymectomy can be estimated as a subpopulation of thymic naive T helper cells (CD3+CD4+CD45RA+CD31+). To perform this task, we evaluated subpopulations of thymic naive T helper lymphocytes with CD3+CD4+CD45RA+CD31+ phenotype in the children (n = 40) who underwent thymectomy during surgical treatment of congenital heart diseases in neonates, or in early postnatal life. Their data were compared with children who underwent surgical treatment of congenital heart disease without thymectomy at the same age periods (n = 12), and healthy children (n = 23). We have revealed that thymectomy in frames of surgery of congenital heart disease leads to reduced thymic naive T helper lymphocytes with CD3+CD4+CD45RA+CD31+ phenotype in peripheral blood. Early execution of thymectomy is associated with deficiency of the thymic naive T helper lymphocytes in the peripheral blood, as well as a decrease in T helper cells (CD3+CD4+). The number thymic naive T helper lymphocytes in peripheral blood negatively corrrelated with terms elapsed after the surgery of congenital heart defects in children.